PENGARUH FAKTOR – FAKTOR PERILAKU WARGA ORGANISASI TERHADAP NIAT PINDAH KARYAWAN HOTEL BINTANG TIGA DI KOTA BATAM - Yuddy Giovanna Priscilla; Baby Ovianty Lim (Jurnal Ekonomi dan Industri, 2023)
This study aims to analyze the relationship between training satisfaction, perceptions of supervisors who listen, organizational citizenship behavior, and intention to move to employees who work in three-star hotels in Batam. The results of the study emphasize the importance of paying attention to factors that influence employee intention to move from the company.